189k views
4 votes
3x - 4y = 7

3x + 2y = -5

When the second equation is subtracted from the first, the resulting equation is _____.
-6y = -12
-6y = 12
-2y = -12
2y = 12

User KarateKid
by
6.1k points

2 Answers

3 votes

Answer:

When the second equation is subtracted from the first, the resulting equation is:

-6y = 12

Explanation:

3x - 4y = 7

3x + 2y = -5

On subtracting second equation from first.

⇒ 3x-4y-3x-2y=7-(-5)

⇒ -6y=12

Hence, when the second equation is subtracted from the first, the resulting equation is:

-6y = 12

User JJoao
by
5.3k points
3 votes

Answer:

-6y = 12

Explanation:

3x - 4y = 7

-(3x + 2y = -5)

---------------------------

distribute the minus sign to all the terms in the second equation

3x - 4y = 7

-3x - 2y = +5

--------------------------

0x -6y = 12


-6y = 12

User Franca
by
5.3k points